Space Matters: Barriers and Enablers for Embedding Urban Circularity Practices in the Brussels Capital Region - Verga, Giulia Caterina; Khan, Ahmed Zaib (Frontiers in Built Environment, 2022)
Cities across Europe are increasing their ambitions to embrace a circular economy. In this context, a wide-ranging landscape of urban circularity practices is emerging. This article aims to elaborate on the spatial factors fostering or hampering the embedding of Urban Circularity Practices (UCPs) in the Brussels Capital Region (BCR). The article thus addresses the following set of questions: What do circularity ambitions imply at the urban scale and what is the landscape of practices aimed at realizing urban circularity? What are the spatial implications of urban circularity practices? What could the role of urban design and spatial planning be in embedding and mainstreaming UCPs? These questions are explored both theoretically, through a literature review, and empirically, through case-study research. We show that access to spaces and land emerges as one of the most recurrent barriers to embedding UCPs in BCR, and in other European cities too. We argue that real estate price is one of the main causes but not the only one. Frictions appear in political agendas where the need for more housing, productive spaces, land for urban agriculture and green-blue infrastructures compete for the same limited space. Concurrently the systematic building of the last available urban ‘void’ (often brownfields) creates perverse logics of rushing the completions of ‘traditional’ urban projects. Temporary occupations, often cited as exemplary circular practices, receive increasing criticism when they become a structural limit to long-term perspectives. We have structured our arguments in four sections. First, we define our notion of urban circularity and UCPs. Secondly, we introduce a methodology and a framework. Thirdly, four types of UCPs are selected for in-depth analysis. We conclude by highlighting potential leverages for working towards a circular spatial design and planning culture that facilitates embedding and mainstreaming urban circularity in the built environment.